Low-Frequency IL23R Coding Variant Associated with Crohn’s Disease Susceptibility in Japanese Subjects Identified by Personal Genomics Analysis - Onodera, Kei (PLoS One, 2015)
BACKGROUND: The common disease-common variant hypothesis is insufficient to explain the complexities of Crohn’s disease (CD) genetics; therefore, rare variants are expected to be important in the disease. We explored rare variants associated with susceptibility to CD in Japanese individuals by personal genomic analysis. METHODS: Two-step analyses were performed. The first step was a trio analysis with whole-exome sequence (WES) analysis and the second was a follow-up case-control association study. The WES analysis pipeline comprised Burrows-Wheeler Aligner, Picard, Genome Analysis Toolkit, and SAMTOOLS. Single nucleotide variants (SNVs)/indels were annotated and filtered by using programs implemented in ANNOVAR in combination with identity-by-descent (IBD), subsequently were subjected to the linkage based, and de novo based strategies. Finally, we conducted an association study that included 176 unrelated subjects with CD and 358 healthy control subjects. RESULTS: In family members, 234,067–297,523 SNVs/indels were detected and they were educed to 106–146 by annotation based filtering. Fifty-four CD variants common to both individuals of the affected sib pair were identified. The linkage based strategy detected five candidate variants whereas the de novo based strategy identified no variants. Consequently, five candidates were analyzed in the case-control association study. CD showed a significant association with one variant in exon 4 of IL23R, G149R [rs76418789, P = 3.9E-5, odds ratio (OR) 0.21, 95% confidence interval (CI) 0.09–0.47 for the dominant model (AA + AG versus GG), and P = 7.3E-5, OR 0.21, 95% CI 0.10–0.48 for AG versus GG, and P = 7.2E-5, OR 0.23, 95% CI 0.10–0.50 for the allele model]. CONCLUSIONS: The present study, using personal genomics analysis of a small CD pedigree, is the first to show that the low-frequency non-synonymous variant of IL23R, rs76418789, protects against CD development in Japanese subjects.